Pengaruh Self Leadership Dan Kematangan Emosi terhadap Disiplin Kerja - Yosua Sagala; Arif Murti (Ecobuss, 2023)
This study aims to determine the effect of self leadership and emotional maturity on employee one of many sharia bank in Pematangsiantar city. This is a quantitative research that use questionnaire as a tool to get data. The questionnaire was distributed to all 32 employees of one of sharia bank in Pematangsiantar city. Researcher use IBM SPSS Statistics 25 to analysed the data. Based on the assumption of alpha 5%, the results show that self leadership together with emotional maturity has a positive effect which means that if self leadership and emotional maturity were to increased then work discipline will increase to. If self leadership were to increased by 1 unit, then work discipline will increase by 54.5%, and if emotional maturity also were to increased by 1 unit, then work discipline will increase by 27.8%.